2022
DOI: 10.3390/info13010017
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Bibliometric Mapping of Network Public Opinion Studies

Abstract: To grasp the current status of network public opinion (NPO) research and explore the knowledge base and hot trends from a quantitative perspective, we retrieved 1385 related papers and conducted a bibliometric mapping analysis on them. Co-occurrence analysis, cluster analysis, co-citation analysis and keyword burst analysis were performed using VOSviewer and CiteSpace software. The results show that the NPO is mainly distributed in the disciplinary fields associated with journalism and communication and public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The third stage (2019–2022) is the burst emerging stage, and the burst words in this stage are molecular dynamics, HCL solution, green, and derivatives . These burst words reflect the molecular dynamics study of ionic liquids, so this stage focuses on the corrosion inhibition properties of ionic liquids through microscopic chemical reactions . There were few researchers in electrochemistry, molecular simulation, polymers, and other related topics; the number of papers was insufficient, and the average citation rate was very low.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third stage (2019–2022) is the burst emerging stage, and the burst words in this stage are molecular dynamics, HCL solution, green, and derivatives . These burst words reflect the molecular dynamics study of ionic liquids, so this stage focuses on the corrosion inhibition properties of ionic liquids through microscopic chemical reactions . There were few researchers in electrochemistry, molecular simulation, polymers, and other related topics; the number of papers was insufficient, and the average citation rate was very low.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Still, related research and analysis are time-consuming and laborious, and the cognitive results sometimes may be subjective. In contrast, bibliometrics methods used visualization software to mine research topics in specific fields, which had become an effective way to explore the hot research and evolution path of the knowledge base. , Therefore, this paper employed bibliometrics and knowledge mapping methods to analyze articles’ application status and trends in the ionic liquid corrosion inhibition field. , And this Review mainly focused on these critical issues: (RQ1) What is the development path of research in the ionic liquid corrosion inhibition field over time? (RQ2) What are the core researchers in ionic liquid corrosion inhibition?…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing other bibliometric papers, it has been observed that the abovementioned countries are also listed among the top contributors for the social media research in the age of COVID-19 [112], COVID-19 vaccination misinformation [40], health-related misinformation in social media [39], and sentiment analysis in times of COVID-19 [115]. Furthermore, it has been observed that both the USA and China have assumed top positions (either first or second position) regarding the contribution to the various fields such as investors sentiments [119], network public opinion [120], sentiment analysis in library and information science [121], social media sentiment in the stock market [122], and the tourism industry [123].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other binary classification methods, the proposed model achieved higher accuracy in using various evaluation measures. Qiang et al [ 13 ] conducted bibliometric analysis and research on NPO and explored the knowledge base and hot trends from a quantitative perspective. They searched 1385 related papers and conducted a bibliometric mapping analysis on them.…”
Section: Literature Reviewmentioning
confidence: 99%